Population density and health condition of Cladocora caespitosa in the shallow zone of the Amvrakikos Gulf (Ionian Sea - Western Greece) - ELENI GAVRIEL; PAVLOS AVRAMIDIS; CONSTANTIN KOUTSIKOPOULOS; ALEXIS RAMFOS (Mediterranean Marine Science, 2026)
The Mediterranean coral Cladocora caespitosa is a key species in temperate marine ecosystems, contributing to reef-building processes. However, it faces increasing threats from climate change, pollution, and human activities, in shallow coastal areas in particular This study presents a baseline monitoring project implemented in the Amvrakikos Gulf, Greece, in order to assess the distribution, health, and environmental drivers of C. caespitosa. A total of 26 sampling sites were surveyed across different depth zones and substrate types. Data collection included photographic documentation, in-situ morphometric measurements, and qualitative assessment of colonies at different substrate types and depths. The results show that the colonies on rocky substrates were significantly larger (118.2 ± 53.0 mm) than those on mixed rocky-sandy substrates (67.7 ± 44.8 mm). The average colony density across sites was 0.217 colonies/m², while only 12.5% of colonies were classified as fully healthy, with 56.05% exhibiting partial mortality. As expected, substrate type and depth were identified as key drivers of coral health and morphology. These findings provide useful baseline insights for conservation and management strategies, particularly for semi-enclosed Mediterranean basins vulnerable to climate change.